2009
DOI: 10.1038/bmt.2009.144
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic crossmatch analysis before allo-SCT is a poor diagnostic tool for prediction of rejection

Abstract: The predictive value of cytotoxic crossmatch analysis before allo-SCT remains unclear. We retrospectively analyzed the clinical impact of cytotoxic T-and B-cell crossmatch testing before allo-SCT between January 2000 and June 2005. Cytotoxic crossmatches were performed in 157 patients receiving stem cells from matched unrelated donors or an HLA-A, -B or -DRB1 allele mismatched graft. Ninety patients are still alive. Eleven patients rejected their grafts. One of 11 patients with rejection was positive in a T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Residual host lymphocytes were detected in 11 of 14 patients with graft failure, suggesting that the mechanism for graft failure could be hostmediated immune rejection. In 2010, Mattsson et al reported that only 1 of 11 patients with allo-HSCT rejection was positive in a T cell CDC crossmatch before allo-HSCT and 4 of 11 in B-cell CDC crossmatches [12]. These poor predictive values are likely because of the fact that even low-or intermediate-titer DSHAs, which fail to cause a positive CDC crossmatch (but can be detected by Luminex testing), can be enough to cause allo-HSCT rejection.…”
Section: Preliminary Evidencementioning
confidence: 99%
“…Residual host lymphocytes were detected in 11 of 14 patients with graft failure, suggesting that the mechanism for graft failure could be hostmediated immune rejection. In 2010, Mattsson et al reported that only 1 of 11 patients with allo-HSCT rejection was positive in a T cell CDC crossmatch before allo-HSCT and 4 of 11 in B-cell CDC crossmatches [12]. These poor predictive values are likely because of the fact that even low-or intermediate-titer DSHAs, which fail to cause a positive CDC crossmatch (but can be detected by Luminex testing), can be enough to cause allo-HSCT rejection.…”
Section: Preliminary Evidencementioning
confidence: 99%